Bimbingan Qur’ani-Ruhani-Islami bagi Perawatan Kesehatan Mental Pasien - M Lutfi; Muhammad Fauzi Rais Lutfi (Alhadharah: Jurnal Ilmu Dakwah, 2022)
The various disturbances and difficulties that a person faces in his life may reduce his physical and mental health, The quality of each person's work is also closely related to the condition of his physical and mental health. If his body is mentally ill, he also suffers from illness which is marked by feelings of anxiety, pale face, decreased enthusiasm, difficulty sleeping, emotional instability, irritability (sensitive), negative thinking, and easily gives up and feels that the illness he is suffering from is a threat to him.Based on the results of surveys and observations conducted at various hospitals around Greater Jakarta and its surroundings, generally when a person experiences a physical disorder that requires him to receive medical treatment at a hospital (patient) will experience disturbances and psychological/mental. Of course, these phenomena and facts are related to the severity and severity of the illness, as well as the length or absence of the treatment period. Therefore, the presence and existence of qur'ani-ruhani-Islamic guidance and mentors as "friends" of patients in mental health care when they are sick is really needed to accompany them and their families who are facing sickness tests from Allah SWT.